2020
DOI: 10.1177/0046958020948668
|View full text |Cite
|
Sign up to set email alerts
|

Elderspeak to Resident Dementia Patients Increases Resistiveness to Care in Health Care Profession

Abstract: Resistiveness to care is very common among patients of dementia as these patients do not take medicines, meals or bath very easily. Indeed, it is a very challenging task for health caregivers and there is a significant rise in time and cost involved in managing dementia patients. Amongst different factors, the type of communication between resident dementia patients and health caregivers is an important contributing factor in the development of resistiveness to care. Elderspeak (baby talk) is a type of communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Receiving neutral or negative care interaction is associated with increased resistiveness to care,14,15 anxiety,16,17 depression,16,17 lower psychological well-being,5 and apathy16 among RwD. Prior research has shown that RwD receive limited care interactions overall, and the interactions that do occur are neutral, task-oriented, and rushed 7,9,15.…”
Section: Overview Of Staff-resident Care Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Receiving neutral or negative care interaction is associated with increased resistiveness to care,14,15 anxiety,16,17 depression,16,17 lower psychological well-being,5 and apathy16 among RwD. Prior research has shown that RwD receive limited care interactions overall, and the interactions that do occur are neutral, task-oriented, and rushed 7,9,15.…”
Section: Overview Of Staff-resident Care Interactionsmentioning
confidence: 99%
“…In contrast, neutral interactions are brief and do not contain pleasant verbal and nonverbal communication, and negative care interactions are restrictive to residents' freedoms or inappropriately controlling due to resident safety concerns. 10 Receiving neutral or negative care interaction is associated with increased resistiveness to care, [14][15][16][17] , anxiety, 18,19 depression, 18,19 lower psychological well-being, 5 and apathy 18 among residents living with dementia. Prior research has shown that residents living with dementia receive limited care interactions overall, and the interactions that do occur are neutral, taskoriented, and rushed.…”
Section: Overview Of Staff-resident Care Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessively slow speech by care providers does not facilitate communication, [39][40][41] and, in fact, "elderspeak" (also called "infantilizing," where caregiver speaks slowly, with elevated pitch, and terms of endearment) can lead to decreased self-esteem and resistiveness to care [42]. More important than slowing of speech is purposeful pacing, allowing time for processing and response formulation.…”
Section: Verbal "Rules Of Engagement"mentioning
confidence: 99%
“…or "patronizing" (usually from individuals who are unfamiliar to the senior resident). It has been found that patients having positive perceptions about "elderspeak" (i.e., words conveyed with warmth from familiar persons) have reported higher levels of self-esteem, reduced agitation, and calmness (Zhang et al, 2020).…”
Section: Nursing Homementioning
confidence: 99%